Some more translation headaches in Romans - du Toit, Andrie B (2010)
Following on a previous article, three more problematic lexical items which occur repeatedly in Romans are discussed: [foreign font omitted] and [foreign font omitted]. Typical of the old, etymological approach, translators are often inclined to attach too much weight to the preposition [foreign font omitted] in [foreign font omitted] In Romans 8:16, for instance, it would be more appropriate to translate [foreign font omitted] in the sense of ‘affirm’: ‘[t]he Spirit of God affirms to our spirit that we are God’s children’. Despite all objections, rendering [foreign font omitted] as ‘Gentiles/Gentile nations’ still remains the best option. In certain contexts in Romans, it would be advisable to translate [foreign font omitted] as ‘I realise/am convinced’. Thereafter some ad hoc problems in Romans 12:6-8; 14:4 and 15:17 are discussed.
Keywords: Bible translations; charismata; Commentaries; etymological fallacy; Gentiles; translation equivalents; Witnessing